Strengthening sustainable english teaching competence by engaging retirees in rural communities - Makhwathana, R. M. (South African Journal of Higher Education, 2025)
Education is one of the fundamental goals of human existence. It is a basic human right. South Africa’s education is for lifelong learning. Engagement of retirees from the community drives active participation and collaboration between Foundation Phase teachers and experienced retirees from the communities. This joint venture benefits both parties with skills, knowledge, values, and attitude transfer and a great opportunity for lifelong learning. It is said that “experience is the best teacher.” A purposive sample of 5 retirees and 5 grade 3 teachers was used to represent the population of this article, comprised of all retirees and all grade 3 teachers in rural communities of Vhembe District. Data was collected through observation and interviews. Thematic analysis was used. Findings revealed that engagement of retirees benefits retirees with improved health and social and financial well-being; thus, retirees should be compensated for their work. Retirees could assist by training and coaching teachers. It is recommended that the Department of Basic Education start engaging retirees to help strengthen teachers’ teaching competence in the English language.